Recalling to Warning:Sosial-Scientific Criticism (SSC) of 1 Corinthians 10:1-13 - Tiffany Tamba (Jurnal Teologi Cultivation, 2020)
AbstractThe meeting of certain cultures and religions with outside cultures and religions results in complex cultural contacts that even overlap. Add more, the high heterogeneity which will affect the process of acculturation, assimilation, inculturation and even enculturation which may increase diversity immunity, but on the contrary triggers sosial irregularities experienced by the Corinthian Christians in 1 Cor. 10: 1-13. The purpose of this study is to see the sosial dynamics of 1 Cor. 10: 1-13 and find the theological message in it by using the interpretation of Sosial-Scientific Criticism (SSC). The use of this method is successful in tracing the sosial aspects that accompany Paul's warnings, advice and message to the diverse Corinthian Christian church. As a result, Paul did a recalling to warning (vv. 1-5) regarding the parallel experiences between his ancestors and them to become learning (vv. 6-10) to then turn to turn (vv. 11-13) towards optimal and total balance. starting with religious regularity, namely loyalty to Allah.